2004
DOI: 10.1097/01.brs.0000120507.36611.8d
|View full text |Cite
|
Sign up to set email alerts
|

Using Magnetic Resonance Imaging to Characterize Pedicle Asymmetry in Both Normal Patients and Patients With Adolescent Idiopathic Scoliosis

Abstract: The baseline used to assess adolescent idiopathic scoliosis vertebral morphology must take into consideration the extent and direction of normal vertebral asymmetry. The pattern of vertebral asymmetry seen inadolescent idiopathic scoliosis may depend on the specific cause of the disorder, with no consistent pattern evident when data from different causes are pooled together.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…We did not statistically analyze the parameters' difference between different genders. Second, all measurements were made from MRI images, which provides for a good evaluation of the vertebral morphology, 6,7 although computer tomography provides finer evaluation of the bony anatomy at the cost of radiation exposure to the patient. Finally, the sample size is relatively small; however, we were limited by the number of patients who had straight normal spines and had an MRI.…”
Section: Discussionmentioning
confidence: 99%
“…We did not statistically analyze the parameters' difference between different genders. Second, all measurements were made from MRI images, which provides for a good evaluation of the vertebral morphology, 6,7 although computer tomography provides finer evaluation of the bony anatomy at the cost of radiation exposure to the patient. Finally, the sample size is relatively small; however, we were limited by the number of patients who had straight normal spines and had an MRI.…”
Section: Discussionmentioning
confidence: 99%
“…O'Brien et al used computed tomography (CT) scans in measuring the width of 512 pedicles in patients with adolescent idiopathic scoliosis (AIS) and found no correlation between age, Risser grade, curve magnitude, axial rotation, and pedicle morphology 34 . Rajwani et al used magnetic resonance imaging (MRI) to evaluate the width of eighty pedicles in patients with AIS and found no correlation between pedicle morphology and location along the convexity or concavity of the curve 30 .…”
mentioning
confidence: 99%
“…The authors of a number of studies have reviewed normal and deformed spines to better understand pedicle morphology [24][25][26][27][28][29][30][31][32] . Parent et al used three-dimensional reconstructions to assess vertebrae in normal and deformed spinal osteologic specimens 33 .…”
mentioning
confidence: 99%
“…Some studies reported inter and intra observer differences during measurements of sagittal spine curvatures [21][22][23]. The differences are due to the inherent anatomical variants that alters the normal spine symmetry from side-to-side [24,25]. In idiopathic scoliosis, asymmetry is primarily demonstrated by vertebral wedging.…”
Section: Introductionmentioning
confidence: 99%